Validating the SONG-PKD Pain Instrument, a Core Outcome Measure for Pain in ADPKD - Rosanna Cazzolli; Angela Ju; Patrizia Natale; Armando Teixeira-Pinto; Martin Howell; Allison Jaure; Ronald D. Perrone; Eva Burnette; Niek F. Casteleijn; Arlene Chapman; Jonathan C. Craig; Sarah Eastty; et al. (Kidney International Reports)
Introduction: Pain is a critically important outcome in autosomal dominant polycystic kidney disease (ADPKD); however, it is infrequently and inconsistently reported in clinical trials. This study aimed to validate the Standardized Outcomes in Nephrology-Polycystic Kidney Disease (SONG-PKD) Pain measure, which includes 3 items related to pain (frequency, severity, and impact on life participation) measured on a 5-point Likert scale, in adults with ADPKD. Methods: A total of 316 adults with ADPKD from 21 countries participated online. The median (interquartile range) age of participants was 56 (44–66) years, 219 (69%) were female, and 222 (70%) had a university degree or higher. Participants completed a demographic questionnaire, brief medical history, and 4 pain measures at baseline. The pain measures were readministered 2 days later. Internal consistency was evaluated with Cronbach’s alpha. Test-retest reliability was assessed using intraclass correlation coefficient (ICC), and convergent validity was assessed using Spearman’s rho. Known groups comparisons for patients with or without a history of kidney complications were performed using a Mann-Whitney rank sum test. Results: The SONG-PKD Pain measure demonstrated high internal consistency (0.94, 95% confidence interval [CI]: 0.93–0.95) and test-retest reliability (0.92, 95% CI: 0.90–0.94). There was a high convergence of SONG-PKD Pain with the Brief Pain Inventory-Short Form (BPI-SF; 0.84, 95% CI: 0.80–0.87) and a visual analog scale (VAS; 0.84, 95% CI: 0.81–0.87). There was a significant difference in the median scores of patients with and without a history of complications (4.0 vs. 0.0, P < 0.001). Conclusion: SONG-PKD Pain instrument is a brief and simple measure that has demonstrated strong psychometric properties.